Retrograde peri‐implantitis: incidence and possible co‐existing factors: a retrospective analysis. (8th August 2022) - Solomonov, Michael; Via, Shlomo; Dinur, Noam; Ben Itzhak, Joe; Lev, Ron; Averbuch Zehavi, Elor; Arbel, Yael; Lvovsky, Alex; Azizi, Hadas; Abadi, Meital; Cohen, Matityahu Neriya; Shemesh, Avi
Abstract: Objectives: To evaluate the incidence of retrograde peri‐implantitis (RPI) generally and the incidence of RPI with an endodontic‐treated adjacent tooth and/or a periapical radiolucency. Method: The retrospective case–control study included the follow‐up periapical images of single dental implants. Two calibrated graduate endodontic residents evaluated simultaneously the presence of RPI and the adjacent teeth status (a previous root canal treatment (RCT) and the periapical status). Results: Six hundred and eleven dental implants were included in this study. Twenty‐three implants with RPI were detected (the incidence of RPI was 3.7%). Thirty‐one adjacent teeth to the implants with RPI were recognized. Out of them, seven teeth had a previous RCT and periapical radiolucency or no RCT and periapical radiolucency. The odds ratios for RPI in an implant with periapical radiolucency or with RCT at the adjacent tooth are 6.67 (95% CI 2.7–16.5), P  < 0.05; and 0.11 (95% CI 0.007–1.9), P  > 0.05 respectively. Conclusions: Based on periapical radiographs, the RPI incidence was 3.7% in the present study. The incidence of RPI increased in cases with adjacent teeth that had periapical radiolucency. Previous RCT in teeth adjacent to implants without apical radiolucency is not correlated with RPI.